2. Artistic Personality in the Light of Socio - Cultural Integration - Rusu Marinela (Review of Artistic Education, 2016)
Artistic personality was interpreted in various ways through the ages. The power of creativity, individual perseverance and imaginative force made the artist a special person, different from most people, being equipped with unique, unrepeatable skills. This paper presents some of the most important approaches to the personality of the creator, from the questionable Freudian theory to the psycho-biological approaches of Peckham. Through his works, the artist expresses not only his personal anxieties or emotional ardent feelings but also, reflects a conscious level of the social group, being himself adapted to human values, characteristic of the era and society to which he belongs. Maybe, sometimes, wrong regarded as deviant personalities or too much exposed to excesses, artists remain, undoubtedly, brave in Creativity, in the cultural and social original development process. Their integration in this ensemble completes the picture we have about development and social evolution, and gives us access to more elevated human values.